The Relationship Between Public Expenditure and Economic Growth In Kosovo: Findings from a Johansen Co-Integrated Test and a Granger Causality Test - Pula, Leke; Elshani, Alban (Ekonomika, 2018)
In the scientific literature, there are two opposing views on the relationship between public expenditure and economic growth. The Keynesian view states that public expenditure is an exogenous factor that influences economic growth and can be used as a policy instrument. This point of view is in contrast to the Wagner view that the public expenditure is seen as an endogenous factor or an outcome, not a cause, of economic growth. The primary objective of this study is to test the views of Keynes’s versus Wagner’s in the case of Kosovo by using Public Expenditure (G), Gross Domestic Product and three other components of GDP: Foreign Direct Investment (FDI), Export (EXP) and Total Budget Revenue (TRtax); the variables used in this analysis are quarterly time series data spanning from 2004–2016. To accomplish the set objectives, the Johansen co-integrated technique is used to investigate the long-run relationship between public expenditure and economic growth, while the Granger causality test is used to know the direction of flow between variables. This study discovers that there is a unidirectional causality between government expenditures and economic growth in Kosovo. It is also found that there is a bidirectional causality between total budget revenue and public expenditure. On the other hand, results also provide evidence that there is a bidirectional causality between export and economic growth. Moreover, the results for Kosovo indicate that data for the period considered support the Keynesian view.
Keywords: public expenditure, economics growth, co-integration, causality, Kosovo